2019
DOI: 10.1093/tas/txz141
|View full text |Cite
|
Sign up to set email alerts
|

Increasing hybrid rye level substituting wheat grain with or without enzyme on growth performance and carcass traits of growing-finishing barrows and gilts

Abstract: New European, fall-planted hybrid rye grown in western Canada is more resistant to ergot and fusarium and has lower content of anti-nutritional factors than common rye. We evaluated the effect of feeding increasing hybrid rye level substituting wheat grain and non-starch polysaccharide (NSP) enzyme inclusion in diets fed to growing-finishing pigs raised under western Canadian commercial conditions. In total, 1,008 pigs (~44 kg body weight [BW]) housed in 48 pens by sex, 21 pigs per pen, were fed diets with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Thacker et al [46] suggest that rye may have much more potential in pig performance when administered in pellet form. Furthermore, to improve feed efficiency and average daily gain, the NSP enzyme would be recommended for diets containing high rye levels [47]. Contrary to the present results, a previous study on the use of rye in pig feeding reported that if more than 50% of the barley or wheat in a swine diet was replaced with rye, a significant reduction in pig performance was observed [50].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Thacker et al [46] suggest that rye may have much more potential in pig performance when administered in pellet form. Furthermore, to improve feed efficiency and average daily gain, the NSP enzyme would be recommended for diets containing high rye levels [47]. Contrary to the present results, a previous study on the use of rye in pig feeding reported that if more than 50% of the barley or wheat in a swine diet was replaced with rye, a significant reduction in pig performance was observed [50].…”
Section: Discussioncontrasting
confidence: 84%
“…Similar results were obtained by Grone [15] and Wilke [14], who observed no negative impact on growth performance when young pigs were fed diets containing a high proportion of rye. Previous studies have shown positive effects of feeding rye on performance data [46][47][48]. Among the beneficial effects of the dietary fiber components in rye, it can provide energy to the pig mostly via the digestion of starch and fermentation of fiber in the hindgut.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rye grain in livestock nutrition is much less frequent (Pieszka et al, 2015). The main concerns in feeding rye grain to animals is its high content of soluble non-starch polysaccharides (mainly arabinoxylans), which increase the viscosity of gastric contents, thus reducing the absorption and bioavailability of nutrients in pigs and poultry (Jürgens et al, 2012;Smit et al, 2019). Compared to wheat, barley or triticale grain, rye grain contains less CP and more dietary fiber (Micek, 2008;Rodehutscord et al, 2016;Krieg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fall planting of hybrid rye maximizes the utilization of crop land, ensures winter soil coverage, and results in an earlier crop than spring-planted cultivars. Hogs responded to xylanase and ß-glucanase inclusion when hybrid rye replaced wheat grain in growout rations (Figure 3; Smit et al, 2019). Distillers' grain (and solubles if included) resulting from ethanol and distillery production is the most common worldwide cereal coproduct fed to domestic animals.…”
Section: Beltranena and Zijlstramentioning
confidence: 99%
“…Cost vs. benefit of feeding increasing hybrid rye level replacing wheat grain with or without enzyme to hogs. Income over feed cost (IOFC) calculated as gross carcass revenue minus feed cost (Smit et al, 2019). Beltranena and Zijlstra Wheat milling to produce flour for human bakery products involves upfront removal of testa components resulting in various coproducts: middlings, shorts, and millrun with proportionally increasing insoluble fibre content.…”
Section: Beltranena and Zijlstramentioning
confidence: 99%